2017
DOI: 10.22159/ajpcr.2017.v10i3.16000
|View full text |Cite
|
Sign up to set email alerts
|

Punica Granatum Rind Extract: Antibiotic Potentiator and Efflux Pump Inhibitor of Multidrug Resistant Klebsiella Pneumoniae Clinical Isolates

Abstract: Objective: With a rise in multidrug resistant (MDR) bacterial isolates, search for antibiotics or compounds that could act synergistically with them is a significant area of research. Efflux-mediated resistance, in particular, is a great hurdle that needs to be overcome. In an effort to identify such synergistic compounds and potential efflux pump inhibitors (EPI), we analyzed the rind of Punica granatum (pomegranate) against MDR clinical Klebsiella pneumoniae isolates.Methods: Sequential fractionation of P. g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The outcome of combining two drugs can be synergistic, additive, or antagonistic depending on the interaction between drugs. Various in vitro experiments have established the fact that a combination of plant extracts and antibiotics possess a synergistic effect, which results in a significant decrease in levels of MIC for the antibiotics [48,49]. One of the main objectives of the current study was to estimate and establish the combined antibacterial activity of plant extracts with antibiotics against clinical strains of periodontal disease causing bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of combining two drugs can be synergistic, additive, or antagonistic depending on the interaction between drugs. Various in vitro experiments have established the fact that a combination of plant extracts and antibiotics possess a synergistic effect, which results in a significant decrease in levels of MIC for the antibiotics [48,49]. One of the main objectives of the current study was to estimate and establish the combined antibacterial activity of plant extracts with antibiotics against clinical strains of periodontal disease causing bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…A number of phytochemicals have proven therapeutic potential as antimicrobial compounds and have also been shown to increase the susceptibility of the organism to various drugs [28,29,31]. In the current study, interaction in antimicrobial activity between two isolated compounds 1 and 3, and in combination with antimicrobial agents, gentamycin and fluconazole was evident.…”
Section: Pd-pdigitatum Rs -Rstolonifermentioning
confidence: 48%
“…A fourfold reduction in the MIC of gentamicin when combined with the phytochemicals, protocatechuic acid, quercetin, caffeic acid on one hand and by the same factor for sulfadiazine in combination with the same compounds on another, in their action against Pseudomonas aeruginosa have been revealed [28]. A 34-fold reduction of MIC of Klebsiella pneumoniae resistant in combination tests involving ethanol extract of Punica granatum rind with ciprofloxacin was demonstrated by Rafiq and coworkers [29]. Allicin, a phytochemical present in garlic, has been shown to work synergistically in combination with β-lactam antibiotics against Staphylococcus spp.…”
Section: Introductionmentioning
confidence: 99%
“…Pomegranate juice and pomegranate oil have antioxidant and anti-inflammatory properties (9,11,16,44). Clinical studies have shown that pomegranate can prevent cancer cell growth in the skin, breast, and prostate (18,45,46). Several in vitro studies have also shown the therapeutic effects of pomegranate extracts on various cancer cells such as breast cancer (MB-MDA and MCF-7), oral cancer (CAL-27 and KB), colon cancer (HT-29), and lung cancer (19)(20)(21)47).…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate seed oil includes a high content of unsaturated fatty acids (e.g., linolenic, oleic acid, starchy acid, palmitic acid, punicic acid), which targets breast cancer cells and kills them usefully (11,16). It also contains antioxidant, anti-carcinogenic, antibacterial, and anti-inflammatory components, which can prevent and treat several cancers, such as colon, lung, and prostate cancer (11,(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%